Brimonidine is Neuroprotective in Animal Paradigm of Retinal Ganglion Cell Damage - Conti, Federica; Romano, Giovanni Luca; Eandi, Chiara Maria; Toro, Mario Damiano; Rejdak, Robert; Di Benedetto, Giulia; Lazzara, Francesca; Bernardini, Renato; Drago, Filippo; Cantarella, Giuseppina; Bucolo, Claudio (Frontiers in Pharmacology, 2021)
To investigate the neuroprotective effect of brimonidine after retinal ischemia damage on mouse eye. Glaucoma is an optic neuropathy characterized by retinal ganglion cells (RGCs) death, irreversible peripheral and central visual field loss, and high intraocular pressure. Ischemia reperfusion (I/R) injury model was used in C57BL/6J mice to mimic conditions of glaucomatous neurodegeneration. Mouse eyes were treated topically with brimonidine and pattern electroretinogram were used to assess the retinal ganglion cells (RGCs) function. A wide range of inflammatory markers, as well as anti-inflammatory and neurotrophic molecules, were investigated to figure out the potential protective effects of brimonidine in mouse retina. In particular, brain-derived neurotrophic factor (BDNF), IL-6, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and its death receptor DR-5, TNF-, GFAP, Iba-1, NOS, IL-1 and IL-10 were assessed in mouse retina that underwent to I/R insult with or without brimonidine treatment. Brimonidine provided remarkable RGCs protection in our paradigm. PERG amplitude values were significantly (p<0.05) higher in brimonidine-treated eyes in comparison to I/R retinas. Retinal BDNF mRNA levels in the I/R group dropped significantly (p<0.05) compared to the control group (normal mice); brimonidine treatment counteracted the downregulation of retinal BDNF mRNA in I/R eyes. Retinal inflammatory markers increased significantly (p<0.05) in the I/R group and brimonidine treatment was able to revert that. The anti-inflammatory IL-10 decreased significantly (p<0.05) after retinal I/R insult and increased significantly (p<0.05) in the group treated with brimonidine. In conclusion, brimonidine was effective in preventing loss of function of RGCs and in regulating inflammatory biomarkers elicited by retinal I/R injury.